Frenz4Frenz youth empowerment campaign : promoting a new approach to fighting youth crime through peer-based interventions - Farin Salleh (2008)
The campaign promoted and raised awareness, among youths, of their untapped power to help peers at risk of committing crimes, and empowered youths to harness that power to positively influence and change their disenchanted friends’ lives for the better.